2013
DOI: 10.1155/2013/716805
|View full text |Cite
|
Sign up to set email alerts
|

Malariometric Indices among Nigerian Children in a Rural Setting

Abstract: Malaria contributes to high childhood morbidity and mortality in Nigeria. To determine its endemicity in a rural farming community in the south-south of Nigeria, the following malariometric indices, namely, malaria parasitaemia, spleen rates, and anaemia were evaluated in children aged 2–10 years. This was a descriptive cross-sectional survey among school-age children residing in a rubber plantation settlement. The children were selected from six primary schools using a multistaged stratified cluster sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
10
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 8 publications
13
10
3
Order By: Relevance
“…The higher prevalence of anaemia in the ≤ five years group with decreasing severity with age is in line with previous studies that anaemia due to malaria is more severe in younger children in areas of intense transmission [25]. Children in this age group are more vulnerable to infection with malaria than others with severe and potentially fatal complications.…”
Section: Discussionsupporting
confidence: 89%
“…The higher prevalence of anaemia in the ≤ five years group with decreasing severity with age is in line with previous studies that anaemia due to malaria is more severe in younger children in areas of intense transmission [25]. Children in this age group are more vulnerable to infection with malaria than others with severe and potentially fatal complications.…”
Section: Discussionsupporting
confidence: 89%
“…However, these studies only took into account urban areas with better quality housing and better access to healthcare facilities. However, in many densely populated urban slums where there is a high degree of poverty, malaria transmission remains high [5, 6]. Our study corroborates these findings with the urban area having the highest malaria burden with parasitaemia being positive and hepatosplenomegaly and anaemia being higher than in the periurban and rural areas.…”
Section: Discussionsupporting
confidence: 87%
“…We have shown a high incidence of asymptomatic carriers with more than half of the population studied being positive for malaria parasitaemia. The prevalence of asymptomatic carriers in this study is much lower than that from a study carried out by Udoh [5] in south-south Nigeria, who found a 71.4% prevalence, and from a previous study carried out in a rural community in Ibadan about 12 years ago, with a prevalence of 80% asymptomatic carriers [19]. …”
Section: Discussioncontrasting
confidence: 85%
“…This is in agreement with the findings of related studies, showing that occurrence of malaria is significantly higher during the period of heavy rainfall in endemic countries of Sub-Saharan Africa [9,16,22].…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of malaria among neonates in this study is 61% and it is comparable to the prevalence rates between 61.1% and 71.4% as reported in previous studies in southern Nigeria [14][15][16] similar prevalence rates have been reported in endemic areas, with a high prevalence of malaria in the first three months of life. The occurrence of malaria in neonates have been attributed to congenital malaria as reported by Sotimehin [17].…”
Section: Discussionsupporting
confidence: 90%